INVESTIGATING INDONESIAN EFL STUDENTS’ LEARNING CHALLENGES - Arfianda, Naufal Farras; Al-Chotibi , Muhammad Akbar; Romadhoni , Ahmad Reza; Hapsari , Hanninda Setyo (Verba: Journal of Applied Linguistics, 2024)
This study explores the students' lacks related to language skills in the English course context as it is an alternative learning place aside from school. It specifically examines the skill the students need to improve. The study was conducted in an English course in Semarang City, Indonesia. The research utilised a descriptive qualitative approach with semi-structured interviews of the course owner who is also the teacher. The findings reveal that there are some shortcomings of the students' language skills namely speaking, writing, grammar, and vocabulary. Furthermore, the English course learning process, trying to improve the students' skills, ensures they can get a good grade in their school. The study concludes that these challenges the students' faced need to be considered by the school by having a more comprehensive learning practice in order to help students improve their language skills.